2020
DOI: 10.4314/ovj.v10i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Drugs, dogs, and driving: the potential for year-round thermal stress in UK vehicles

Abstract: Background: Dogs are regularly transported or housed in vehicles, with guidelines for housing dogs suggesting that the ambient temperature should be maintained between 15°C and 24°C. Veterinary drugs are routinely stored and carried in vehicles providing ambulatory veterinary care. Non-refrigerated medications typically require storage between 8°C and 25°C.Aim: This study aims to investigate the potential for thermal stress associated with vehicular storage and transportation of drugs and dogs in a temperate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Transportation is another crucial issue for working dogs' management, because it has been proven to be stressful and its familiarisation needs a positive early exposure in life [17]. Luckily, 86.4% of handlers and dogs usually travelled in air-conditioned cars or vans, avoiding the warmer seasons and the onset of heatstroke, a pathological condition often reported in working dogs [19].…”
Section: Discussionmentioning
confidence: 99%
“…Transportation is another crucial issue for working dogs' management, because it has been proven to be stressful and its familiarisation needs a positive early exposure in life [17]. Luckily, 86.4% of handlers and dogs usually travelled in air-conditioned cars or vans, avoiding the warmer seasons and the onset of heatstroke, a pathological condition often reported in working dogs [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, vehicular HRI events also occurred on days when the maximum recorded WBGT was <10 °C. Internal vehicle temperatures are predominantly influenced by solar radiation [ 43 ], and UK vehicles have been reported to exceed the upper limit of the canine thermoneutral zone (35 °C) between April and September and exceed 50 °C between May and August [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that dogs with vehicular HRI had three times the odds for severe HRI compared to dogs with exertional HRI. This is likely due to several important differences between exertional and vehicular HRI, primarily that dogs confined to hot vehicles have no opportunity to escape the heat and can be exposed to more extreme temperatures [ 44 ]. Dogs that develop exertional HRI are also more likely to do so in the presence of their owner who can take steps to limit progression of the condition such as ceasing the exercise, seeking shade, and initiating active cooling with water.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular importance to note is the regular occurrence of working dogs being forgotten and left in unattended vehicles for extended periods, leading to their death when heat and dehydration impact without sufficient ventilation, hydration or cooling in place. In response to the climate crises and global warming, vehicle transportation has been identified as a risk for dogs, even in areas not traditionally considered hot, such as the United Kingdom (121).…”
Section: Transportationmentioning
confidence: 99%